1987
DOI: 10.1677/joe.0.1150241
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related differences in renal size in mice: ontogeny and influence of neonatal androgens

Abstract: Kidneys of adult male mice are larger than those of females because of both cellular hyperplasia and hypertrophy. Administration of testosterone to adult female mice induced cellular hypertrophy but not hyperplasia, so that the weight of the kidney remained smaller than in male mice. The sexual dimorphism in kidney size is not congenital but programmed by neonatal endogenous androgens and expressed between 30 and 40 days of age. Treatment of newborn males with cyproterone acetate and of newborn females with te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…(e) By immunoelectron microscopy, ER were found in the nuclei of proximal tubule cells in both M and F rats [62], whereas in tissue sections of rat and mouse kidneys, AR were detected by immunocytochemistry in the nuclei of distal nephron [246]. (f) In the cytosolic fraction of mouse kidney cortex and cultured proximal tubule cells, AR were detected by binding assay of 3 H-dihydrotestosterone (DHT) [176], and (g) in human kidneys, ERβ were localized by immunocytochemistry to the collecting duct in M [255] or by in situ hybridization in the M and F cortex and medulla PT and DT cells that appear after puberty [100,143,161,169,177,194,219] Size of kidney cortex Rat F < M Androgen-induced hypertrophy of PT [22,177] Size of PT cells [22,161,194] Urine production Rat, mouse F > M Higher water consumption in F [124,216,271] Urine protein Rat, mouse F < M Androgen-dependent production and secretion of α-and β-microglobulins in PT and, possibly, a higher rate of endocytosis in F [4,102,194] Urine angiotensinogen Rat F < M Androgen-stimulated production and secretion of angiotensinogen (transport via exocytosis in PT?) [270] Urine vasopressin Rat, human F < M Reflects the plasma vasopressin levels (F < M).…”
Section: Sex Hormone Receptors In the Kidneymentioning
confidence: 99%
“…(e) By immunoelectron microscopy, ER were found in the nuclei of proximal tubule cells in both M and F rats [62], whereas in tissue sections of rat and mouse kidneys, AR were detected by immunocytochemistry in the nuclei of distal nephron [246]. (f) In the cytosolic fraction of mouse kidney cortex and cultured proximal tubule cells, AR were detected by binding assay of 3 H-dihydrotestosterone (DHT) [176], and (g) in human kidneys, ERβ were localized by immunocytochemistry to the collecting duct in M [255] or by in situ hybridization in the M and F cortex and medulla PT and DT cells that appear after puberty [100,143,161,169,177,194,219] Size of kidney cortex Rat F < M Androgen-induced hypertrophy of PT [22,177] Size of PT cells [22,161,194] Urine production Rat, mouse F > M Higher water consumption in F [124,216,271] Urine protein Rat, mouse F < M Androgen-dependent production and secretion of α-and β-microglobulins in PT and, possibly, a higher rate of endocytosis in F [4,102,194] Urine angiotensinogen Rat F < M Androgen-stimulated production and secretion of angiotensinogen (transport via exocytosis in PT?) [270] Urine vasopressin Rat, human F < M Reflects the plasma vasopressin levels (F < M).…”
Section: Sex Hormone Receptors In the Kidneymentioning
confidence: 99%
“…This is consistent with previous studies, both animal and human, that have demonstrated glomerular number is significantly linked to gender. [34][35][36] In addition, we saw no changes in 24-h MAP and HR in Mg 2+ -deficient offspring. These findings were quite unexpected, as maternal deficiencies in other trace elements such as zinc 37 and iron 38,39 are known to reduce nephron number and increase BP in the adult offspring.…”
Section: Discussionmentioning
confidence: 60%
“…The larger kidneys in males than females may be due to increased body weight, but the size of the kidney may also correlate with other factors associated with androgens. According to some authors, kidneys of adult male mice were larger than those of females, because of both the cellular hyperplasia and hypertrophy due to the influence of androgens [10]. In addition, the length of the right kidney was greater than that of the left kidney, but opposing to those reported in dogs (the cranial margin of the right kidney was not clearly outlined for measurement in all dogs) [15].…”
Section: Discussionmentioning
confidence: 99%